Control system and control method for power factor improvement of wound-type asynchronous motor - YAO LEIBO; JI XUANDE; DUAN XIAOMING; DUAN CHUNXIA; WU CHAO; GUO LONGGANG; HE YONG (2019)
The invention relates to a control system and control method for power factor improvement of a wound-type asynchronous motor. The control system comprises a KM1 contactor, a KM2 contactor, R startresistors, boosting transformers, adjustable capacitors, a rotor speed measuring circuit, a CPU controller, a driver and an actuator, wherein the rotor speed measuring circuit is respectively connected with the wound-type asynchronous motor and the CPU controller, the driver is respectively connected with the CPU controller and the actuator, the actuator is connected with the a-phase boosting transformer secondary-side adjustable capacitor, the b-phase boosting transformer secondary-side adjustable capacitor and the c-phase boosting transformer secondary-side adjustable capacitor, the a-phaseboosting transformer primary side, the b-phase boosting transformer primary side and the c-phase boosting transformer primary side are all connected with the KM2 contactor, and the KM1 contactor is connected with the a-phase, b-p